Arthrogryposis in piglets - Leipold, H.W.; Ely, R.; Schoneweis, D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This report documents experimental reproduction of tetramelic arthrogryposis in purebred Yorkshire swine by breeding trials. Data from the trials indigated arthrogryposis may be due to homozygosity of a simple autosomal recessive gene. No affected pig was observed to be alive at parturition, although most had been alive in utero just prior to delivery. Other than dystocia observed in the sows, no other significant clinical findings were noted. The condition was noted in five litters from two sows which were bred to the same boar. Approximately 25% of the pigs exhibited the clinical signs of arthrogryposis which included malformed rigidly extended legs.
Keywords: Swine; Arthrogryposis; Piglets; Dystocia